Topical Timolol for Infantile Haemangioma of the Orbit - Hildebrand, Göran Darius; Sipkova, Zuzana (Klinische Monatsblätter für Augenheilkunde, 2021)
Infantile haemangiomas (IHs) are the most common benign tumours of the eyelid and orbits in infancy. Beta-blockers, in the form of oral propranolol, have become first-line treatment in severe cases with functionally significant or disfiguring IH. However, adverse drug reactions of oral propranolol in infants are reported in 1 in 11 and serious or potentially life-threatening systemic side effects in 1 in 38, including dyspnoea, hypotension, hyperkalaemia, hypoglycaemia, and cyanosis, therefore requiring careful and close monitoring during the course of systemic treatment. More recently, two large meta-analyses have shown topical beta-blockers, such as timolol maleate 0.5%, to be as effective as oral propranolol in superficial IH, but with no or significantly fewer adverse effects, and have advocated that topical beta-blockers replace oral propranolol as the first-line treatment of superficial IH. We have previously reported the therapeutic response of deep periocular IH to primary topical timolol maleate 0.5% monotherapy. Here we also describe the first successful treatments of large orbital IHs with primary topical timolol maleate 0.5% monotherapy in four infants, resulting in immediate cessation of progression and rapid clinical improvement or resolution in all cases. No adverse effects and no recurrence during long-term follow-up of up to 2.5 years after cessation were seen in any of the patients treated with topical timolol maleate 0.5%.
Keywords: topical timolol; beta-blockers; orbital infantile hemangioma; orbital infantile haemangioma; orbital capillary haemangioma